Weight loss in female wrestlers: observations and recommendations from a competitor and coach - Shai, K. (International Journal of Wrestling Science, 2025)
Weight cutting is the perceived equalizer in wrestling. We have used it to build resilient, disciplined athletes and humans. For some, weight cutting becomes a persona, for others, simply a means to a goal. Despite our unavoidable entanglement with managing weight, it is often the most misunderstood and mismanaged part of the wrestling experience. This is becoming especially true for girls and women. My experience as an athlete has given me the opportunity to see weight cutting and weight management from all angles. I was a 7-time U.S. National Team Member (add a covid year and many years on the sidelines due to surgeries), a World University Champion, and a 2-time Olympic Team alternate. I`ve experienced the emotional highs of victory and the physical lows of poor weight management. Now, as a coach and founder of LuchaFit, I work with the next generation of female wrestlers and their support systems to ensure they don`t make the same mistakes I did, or the mistakes of others I witnessed far too often. Throughout my career, I saw athletes with bright futures break down after repeat cuts and never see out their potential. I witnessed hidden disordered eating, and chronic under-fueling. The unfortunate truth I observed was the habits of the women at the top level, trickling down to our development and youth wrestlers. I also discovered how proper nutrition, a grounded mindset, and phase-specific adjustments could transform the weight cut process and enhance performance.. What`s missing in most wrestling rooms isn`t cranking up the heat up, it`s education. This commentary is meant to bridge the gap. Pulling from my personal experience, as well as the science behind female physiology, I created a comprehensive guide to help female wrestlers manage their weight safely and sustainably. I will be summarizing the core principles from that guide, offering insights and recommendations to support athletes, coaches, parents, and the team behind them.